Decarbonisation using fuel switching in freight transport: a case of Kenya - Kariuki, D. N. (Strathmore University, 2025)
Traditionally, the transportation sector has relied on fossil fuels such as coal, petroleum and natural gas. However, the urgent need to reduce greenhouse gas (GHG) emissions has prompted a global shift towards renewable energy sources. In Kenya, the transportation of freight cargo is predominantly done by trucks that rely on diesel as their main energy source. The nation has made several efforts to mitigate these increase in emissions such as the promotion of electric vehicles, the development of the National Climate Change Action Plan (NCCAP), provision of non-motorised transport (NMT) infrastructure and international commitments like the COP 26 declaration that aims to accelerate the transition to 100% zero carbon vehicles. Furthermore, research on mitigating transport emissions has been carried, however some researchers focused on modal shift, other scholars focused on shifting only passenger cars while others focused on one fuel switch option only. This study’s objective was to analyse the current road sector emissions associated with freight transport, primarily HGVs. In this study, fuel switching options for HGVs were modelled. The model was based on the Avoid-Shift-Improve (ASI) theory which had three (3) scenarios, the Business as Usual (BAU), centralise scenario and the improve scenarios. The study concluded that the BAU scenario should not be allowed to continue and policy changes were necessary to mitigate its emissions. In the centralise scenario, the emissions were similar to that of the BAU reporting just a 2.3% reduction in emissions by 2050. The improve scenario was seen as the most promising scenario in CO2 abatement recording 16.4% reduction in CO2 emissions by 2050. Keywords: Freight transport, fuel switch, decarbonisation, Kenya, CO2 reduction, well to wheel emissions, Avoid-Shift-Improve.
Full - text thesis